Proceedings of the 2019 5th International Conference on Social Science and Higher Education (ICSSHE 2019) 2019
DOI: 10.2991/icsshe-19.2019.239
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Different Corrective Feedback on College English Learners’ Acquisition of Subjunctive Mood

Abstract: The study mainly investigates the effectiveness of explicit feedback and implicit feedback on college English learners' acquisition of subjunctive mood. In an experimental design (two treatment groups and one control group), 120 non-English major students completed four communicative activities during which they received either metalinguistic feedback (explicit feedback) or recasts (implicit feedback) or no feedback from the teacher in case of any erroneous utterance in the target grammar structure. Three pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Zhang (2020) found that learners' native language background, personality, language level and other factors would affect their understanding and response to Corrective Feedback and their choice of Corrective Feedback mode. Zhang (2016) found that high-level learners can benefit from two different forms of feedback, while indirect feedback has a more obvious effect on low-level learners, which may be because indirect feedback reduces the difficulty of tasks by delineating error areas, indicating error categories and providing feedback functions such as rule interpretation.…”
Section: The Relationship Between Feedback Effect and Individual Lear...mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang (2020) found that learners' native language background, personality, language level and other factors would affect their understanding and response to Corrective Feedback and their choice of Corrective Feedback mode. Zhang (2016) found that high-level learners can benefit from two different forms of feedback, while indirect feedback has a more obvious effect on low-level learners, which may be because indirect feedback reduces the difficulty of tasks by delineating error areas, indicating error categories and providing feedback functions such as rule interpretation.…”
Section: The Relationship Between Feedback Effect and Individual Lear...mentioning
confidence: 99%
“…After comparing the effect of explicit recasting and implicit recasting on middle school students' grammar, Guo (2013) concluded that explicit recasting is the best choice for teachers compared with implicit recasting. Zhang (2016) found that compared with implicit feedback and input feedback, explicit feedback and output feedback help learners to pay more attention to the target language, make them better notice the gap between the current language structure and the target language structure, and ultimately affect the effectiveness of feedback.…”
Section: Effectiveness Of Different Feedback Classificationmentioning
confidence: 99%